188k views
4 votes
Can you help please?

(4x + 3) - (5x-7)

User Raner
by
5.2k points

2 Answers

2 votes

Answer:

(4x +3) - (5x - 7) (distribute the - sign through the second expression and drop the parenthesis)

4x +3 -5x +7 (combine like terms. subtract 5x from 4x and add 3 and 7)

-x +10 (this is your answer)

Explanation:

User Don Cruickshank
by
5.1k points
0 votes

Answer: -x + 10

===============================

Work Shown:

(4x+3) - (5x-7)

4x+3 - 5x+7 ..... distribute the negative

(4x-5x) + (3+7)

-x + 10

User JoJoeDad
by
5.8k points